2005
DOI: 10.1161/circulationaha.104.528455
|View full text |Cite
|
Sign up to set email alerts
|

Volume-Outcome Relationships for Percutaneous Coronary Interventions in the Stent Era

Abstract: Higher-volume operators and hospitals continue to experience lower risk-adjusted PCI outcome rates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
150
2
3

Year Published

2006
2006
2011
2011

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 173 publications
(159 citation statements)
references
References 22 publications
4
150
2
3
Order By: Relevance
“…Based on the intuitive concept that ''practice makes perfect'' and supported by the demonstration of such relations with surgical procedures, the linkage of operator and institutional volume to PCI quality has been assumed [25][26][27][28][29][30][31][32][33].…”
Section: Public Reporting Of Pci Volumementioning
confidence: 99%
“…Based on the intuitive concept that ''practice makes perfect'' and supported by the demonstration of such relations with surgical procedures, the linkage of operator and institutional volume to PCI quality has been assumed [25][26][27][28][29][30][31][32][33].…”
Section: Public Reporting Of Pci Volumementioning
confidence: 99%
“…This relationship has been confirmed during both the pre-and post-stent eras (4). The ESPRIT dataset suggests that procedural outcome after PCI is a function of institutional volume, but not operator volume.…”
Section: Discussionmentioning
confidence: 76%
“…Many US-based studies have reported a strong inverse relationship between annual PCI volumes performed by an individual physician or institution and clinical outcomes after PCI (1)(2)(3)(4)(5)(6). This relationship has been confirmed during both the pre-and post-stent eras (4).…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…Even in the stent era, an inverse relationship between hospital PCI volume and in-hospital outcome has been reported to be preserved, especially for emergency procedures. 8,9) However, several reports from Japan showed there was no significant relationship between hospital volume and in-hospital outcome among AMI patients undergoing PCI. 10,11) Since not all STEMI patients can always present at highvolume centers that comply with the guideline, cardiologists belonging to PCI centers in a local area must perform primary PCI for STEMI patients in as timely a manner as possible even if their PCI volume does not meet with the guideline criteria.…”
Section: Discussionmentioning
confidence: 99%